An Open IoT Platform to Promote Eco-Sustainable Innovation in Western Africa: Real Urban and Rural Testbeds. (1st August 2018) - Dupont, Corentin; Vecchio, Massimo; Pham, Congduc; Diop, Babacar; Dupont, Charlotte; Koffi, Sename
Abstract : The digital revolution led by the Internet of Things (IoT) is already reshaping several traditional business sectors. Moreover, because of its very nature, the promise of the IoT is also to reduce energy consumption and pollutant emissions in several environmental scenarios. At the same time, it is desirable to keep the development of IoT as sustainable as possible, hence truly realizing the vision of the green IoT . In this paper, we show how a full-stack IoT framework can alleviate some real environmental problems afflicting countries in Western Africa. We present three real IoT-based deployments currently hosted in two rural areas of Senegal and Ghana and one metropolitan area of Togo. These testbeds are connected to a Cloud-based software platform, purposely designed and engineered to address some very specific environmental, economic, and social requirements of the region.